Volume 7B: Structures and Dynamics 2014
DOI: 10.1115/gt2014-26478
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Compressor Rotor Non-Synchronous Vibration With and Without Fluid-Structure Interaction

Abstract: This paper study the non-synchronous vibration (NSV) of a high speed multistage axial compressor using rigid blade and vibrating blade with fluid-structural interaction (FSI). The unsteady Reynolds-averaged Navier-Stokes (URANS) equations and mode based structural dynamic equations are solved. A low diffusion E-CUSP Reimann solver with a 3rd order WENO scheme for the inviscid fluxes and a 2nd order central differencing for the viscous terms are employed. A 1/7th annulus sector of IGV-rotor-stator is used with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The blade vibration is attributed to the oscillating blade tip vortex by Hwang et al [ 13 ]. By using the model of Kielb [ 14 ], studies have been carried out by Zha et al [ 15 , 16 , 17 , 18 , 19 , 20 ] to explore the flow at tips. The results reveal that the tip clearance shape has an influence on the frequency of NSV [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blade vibration is attributed to the oscillating blade tip vortex by Hwang et al [ 13 ]. By using the model of Kielb [ 14 ], studies have been carried out by Zha et al [ 15 , 16 , 17 , 18 , 19 , 20 ] to explore the flow at tips. The results reveal that the tip clearance shape has an influence on the frequency of NSV [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oscillation by the vortex coming and leaving generates a torsion moment, coupling with the blade structure in modal vibration [ 18 ]. Simulations [ 19 , 20 ] coupled with fluid and structure studies indicate that the blade vibration exhibits a limit cycle oscillation excited by the aerodynamic force, but the comparison results also show that the first torsion mode observed in the rig test is accompanied by the first bending vibration of the blade, which is not obvious in the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Vahdati et al [15] used the fully-coupled approach to explain the stall and acoustic flutter mechanisms of the wide-chord fan blade. Gan et al [16] adopted the fully-coupled fluid-structure interaction method to investigate the non-synchronous vibration of a compressor rotor. Phan and He [17,18] used the fully-coupled method to elucidate the vibration mechanisms of the structurally and aerodynamically mistuned cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Zha et al [ 14 , 15 , 16 , 17 , 18 , 19 ] carried out a series of works with the same compressor of Kielb [ 2 ], established 1/7th and full annulus models for the 1.5-stage compressor. The RANS simulations [ 14 ] show that the tip clearance shape has a strong influence on the frequency of NSV.…”
Section: Introductionmentioning
confidence: 99%
“…Pay attention to the interaction of fluid and structure, the applications of the time-domain FSI method have been taken into practice to research related contents. The computations [ 18 , 19 ] are conducted to investigate the NSV by comparing the flow excitation with rigid blades and the blade vibration with fluid–structure interaction. It is indicated that the NSV of the compressor is caused by the tornado-like tip vortex in the rotor tip as rotating flow instability.…”
Section: Introductionmentioning
confidence: 99%